Preparation method of nano Fe-MOF material and nano MOFs material
By ultrasonically reacting iron salts and 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid ligands in an aqueous phase, combined with STB additives, nano-Fe-MOF materials with uniform size and good chemical stability were successfully prepared. This solved the problems of long synthesis time, high cost, inhomogeneity and poor stability in the existing technology, and achieved green and efficient synthesis.
Patent Information
- Application Number
- CN202511095725.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-11-21
AI Technical Summary
Existing methods for synthesizing nano-MOFs materials suffer from problems such as long reaction times, high costs, uneven product sizes, and poor chemical stability, making it difficult to achieve green and efficient synthesis.
Nano-Fe-MOF materials were synthesized by ultrasonic reaction of iron salt, 2,5-bis(1,2,4-triazol-1-yl) terephthalic acid ligand and strong basic organometallic compounds in an aqueous phase. The particle size was controlled by STB additive to form a three-dimensional framework structure with one-dimensional irregular channels.
This study achieved good size uniformity and chemical stability of nano-MOF materials, with a friendly synthesis environment, high reaction efficiency, high yield, and low cost.
Smart Images

Figure CN120988296A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of metal-organic framework (MOF) materials, specifically to a nano-Fe-MOF material and a method for preparing nano-MOF materials. Background Technology
[0002] MOFs are porous crystalline hybrid materials composed of metal ions and organic ligands. Nano MOFs refer to MOF materials with at least one dimension of nanoscale (1-1000 nm) at the microscopic level, and they have promising applications in catalysis, medicine, energy, and other fields.
[0003] Commonly used methods for synthesizing nanoscale MOFs include surfactant-mediated hydrothermal synthesis, reverse microemulsion synthesis, and template synthesis. Surfactant-mediated solvothermal synthesis involves adding surfactants such as CTAB (cetyltrimethylammonium bromide) and PVP (polyvinylpyrrolidone) under solvothermal conditions to inhibit crystal growth and stabilize nanoparticles. However, this method generally has a long reaction time, may use toxic organic solvents, and produces products with uneven size distribution and relatively low quality. Reverse microemulsion synthesis involves forming nanodroplets in an oil-water-surfactant system to restrict the growth space of MOFs, yielding nanoparticles (typically <100 nm). However, this method is generally very expensive, limited by the microemulsion system, has low yield, and requires the addition of emulsifiers or dispersants, making it only suitable for small-scale laboratory synthesis. Template synthesis involves adding template agents such as SiO2 nanospheres to the reactants to control size. However, this method is difficult to precisely control size, results in numerous crystal defects, reduced stability, and complete template removal is challenging. Summary of the Invention
[0004] In view of this, this disclosure provides a method for preparing nano-Fe-MOF materials and nano-MOFs materials, realizing the green and efficient synthesis of nano-MOFs materials with uniform size, good chemical stability, and simple process with low preparation cost.
[0005] To achieve the aforementioned objectives, in a first aspect, the present disclosure provides a nano-Fe-MOF material, wherein the material is an aqueous ultrasonic reaction product of an iron salt, a 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid (H2BTTA) ligand, and a strongly basic organometallic compound, and has the molecular formula C0. 12 H8N6O4 crystallizes in the triclinic crystal system, space group P-1. The asymmetric unit of the crystal contains one iron ion and one completely deprotonated BTTA. 2-The ligand and an undeprotonated H2BTTA ligand, a six-coordinated Fe ion with two O atoms and four N atoms form an octahedral coordination environment, a six-connected Fe monometallic node and a four-connected BTTA ligand 2- The ligand H2BTTA, which is linked to the two, coordinates to form a three-dimensional framework structure with one-dimensional irregular channels.
[0006] Preferably, the iron salt is one of ferric chloride, ferric acetylacetone, ferric sulfate, and ferric nitrate;
[0007] The strongly alkaline organometallic compound is sodium alkoxide or potassium alkoxide;
[0008] The molar ratio of the iron salt to the ligand is 1:(0.2-2).
[0009] Preferably, the iron salt is ferric chloride;
[0010] The sodium alkoxide is sodium tert-butoxide, sodium methoxide or sodium ethoxide, and the potassium alkoxide is potassium tert-butoxide;
[0011] The molar ratio of the iron salt to the ligand is 1:1.
[0012] Preferably, the sodium alkoxide is sodium tert-butoxide;
[0013] The ultrasonic power is 200-800W;
[0014] The reaction time is 5-90 min.
[0015] Preferably, the ultrasonic power is 600W;
[0016] The reaction time is 5 minutes.
[0017] Secondly, this disclosure provides a method for preparing nano-MOF materials, including:
[0018] The reaction system consisting of a metal salt, ligand, sodium or potassium alkoxide auxiliaries, and water is carried out under ultrasonic conditions.
[0019] The target product is obtained by drying the solid phase product in the reaction product.
[0020] Preferably, the metal salt is one of cerium ammonium nitrate, zirconium chloride, and magnesium nitrate;
[0021] The additive is STB.
[0022] Preferably, the ligand is one of terephthalic acid, gallic acid, fumaric acid, 4,4'-dicarboxylic acid diphenyl ether, 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid, and 2,5-dihydroxy-1,4-benzoquinone.
[0023] Preferably, the molar ratio of the metal salt to the ligand is 1:(0.2-2).
[0024] Preferably, the ultrasonic power is 200-800W;
[0025] The reaction time is 5-90 min.
[0026] The beneficial effects of this invention are:
[0027] This invention discloses a novel nano-Fe-BTTA material, which, compared with conventional nano-Fe-MOFs materials, exhibits uniform material size, significantly smaller particle size, higher product quality, and excellent chemical stability. Furthermore, this invention provides a method for preparing nano-MOFs materials, characterized by synthesis based on an aqueous ultrasonic process with STB additives. This method is environmentally friendly, has high reaction efficiency and yield, produces a uniform target product with a narrow size distribution, and features a simple process and low preparation cost. Attached Figure Description
[0028] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the specification, serve to illustrate the technical solutions of this disclosure.
[0029] Figure 1 The synthesis route of the nano-Fe-BTTA material in Example 1 of this invention is shown below;
[0030] Figure 2 This is a schematic diagram of the structure of the nano-Fe-BTTA material in Embodiment 1 of the present invention, wherein (a) is a coordination environment diagram of the metal and ligands; (b) is a three-dimensional packing diagram in the first direction; and (c) is a three-dimensional packing diagram in the second direction.
[0031] Figure 3 The images show the XRD patterns of the nano-Fe-BTTA materials of Comparative Example 1 and Example 1 of this invention.
[0032] Figure 4 This is a structural stability test diagram of the nano-Fe-BTTA material in Example 1 of the present invention;
[0033] Figure 5 These are SEM images of the nano-Fe-BTTA materials of Comparative Example 1(a) and Example 1(b) of this invention;
[0034] Figure 6 The figures show the Zeta potentials of the nano-Fe-BTTA materials in Comparative Example 1(a) and Example 1(b) of this invention.
[0035] Figure 7 The particle size distribution diagrams of the nano-Fe-BTTA materials in Comparative Example 1(a) and Example 1(b) of this invention are shown.
[0036] Figure 8 The images show the XRD patterns of the nano-MOFs materials of Comparative Example 19(a) and Example 19(b) of this invention.
[0037] Figure 9 SEM images of the nano-MOFs materials of Comparative Example 19(a) and Example 19(b) of the present invention;
[0038] Figure 10 The images show the XRD patterns of the nano-MOFs materials of Comparative Example 20(a) and Example 20(b) of this invention.
[0039] Figure 11 These are SEM images of the nano-MOFs materials of Comparative Example 20(a) and Example 20(b) of the present invention;
[0040] Figure 12 The images show the XRD patterns of the nano-MOFs materials of Comparative Example 21(a) and Example 21(b) of this invention.
[0041] Figure 13 These are SEM images of the nano-MOFs materials of Comparative Example 21(a) and Example 21(b) of the present invention;
[0042] Figure 14 The images show the XRD patterns of the nano-MOFs materials of Comparative Example 22(a) and Example 22(b) of this invention.
[0043] Figure 15 These are SEM images of the nano-MOFs materials of Comparative Example 22(a) and Example 22(b) of the present invention;
[0044] Figure 16 The images show the XRD patterns of the nano-MOFs materials of Comparative Example 23(a) and Example 23(b) of this invention.
[0045] Figure 17 The images show SEM images of the nano-MOFs materials of Comparative Example 23(a) and Example 23(b) of this invention. Detailed Implementation
[0046] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0047] This disclosure provides a nano-Fe-BTTA and its preparation method, as detailed below:
[0048] Figure 1 This discloses the synthetic route for nano-Fe-BTTA materials, combined with Figure 1 As shown, the nano Fe-BTTA material is a product synthesized from iron salt, 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid (H2BTTA) ligand, and sodium tert-butoxide (STB) in an aqueous phase under ultrasonic conditions.
[0049] In a specific embodiment, the preparation method of the nano Fe-BTTA material is as follows: FeCl3 and H2BTTA are weighed and placed in a wire-sealed reagent bottle according to the ratio of FeCl3:H2BTTA:STB = 1:1:1. Then, STB is weighed and added to the wire-sealed reagent bottle, and ultrapure water is added. The ultrasonic machine is turned on for synthesis, the reaction time is 5 minutes, and the ultrasonic machine power is set to 600W.
[0050] After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0051] In a specific embodiment, the iron salt is one of ferric chloride, ferric acetylacetone, ferric sulfate, and ferric nitrate; the molar ratio of the iron salt to the H2BTTA ligand is 1:(0.2-2).
[0052] In a specific embodiment, the ultrasonic frequency is 40kHz, the ultrasonic power is 200-800W, and the reaction time is 5-90min.
[0053] This disclosure also provides a method for preparing nano-MOF materials, including the following steps:
[0054] The reaction system consisting of a metal salt, ligand, sodium or potassium alkoxide auxiliaries, and water is carried out under ultrasonic conditions.
[0055] The reaction product is subjected to suction filtration or centrifugation, and the resulting solid product is dried in an oven or freeze-dried to obtain the target product.
[0056] The sodium alkoxide additive is sodium tert-butoxide, sodium methoxide, or sodium ethoxide, and the potassium alkoxide additive is potassium tert-butoxide; preferably, sodium tert-butoxide (STB).
[0057] The metal salt is one of ferric chloride, ferric acetylacetone, ferric sulfate, ferric nitrate, cerium ammonium nitrate, zirconium chloride, and magnesium nitrate.
[0058] The ligand is one of terephthalic acid, gallic acid, fumaric acid, 4,4'-dicarboxylic acid diphenyl ether, 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid, and 2,5-dihydroxy-1,4-benzoquinone.
[0059] The molar ratio of the metal salt to the ligand is 1:(0.2-2).
[0060] The ultrasonic power is 200-800W; the reaction time is 5-90min.
[0061] The following are preferred embodiments and comparative examples of the synthesis of nano-Fe-BTTA according to this disclosure.
[0062] Comparative Example 1:
[0063] Nano-Fe-BTTA was prepared without the use of STB.
[0064] 1. Weigh 2 mol FeCl3 and 2 mol H2BTTA into a 25 mL thread-sealed reagent bottle, add 20 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 5 min, and the sonicator power is set to 600 W.
[0065] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0066] Example 1:
[0067] Nano-Fe-BTTA was prepared using STB.
[0068] 1. Weigh 2 mol FeCl3 and 2 mol H2BTTA (2,5-bis(1,2,4-triazol-1-yl)terephthalic acid) into a 25 mL sieve-sealed reagent bottle. Then weigh 2 mol STB and add it to the sieve-sealed reagent bottle along with 20 mL of ultrapure water. Turn on the sonicator to synthesize the mixture. The reaction time is 5 min and the sonicator power is set to 600 W.
[0069] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0070] Single-crystal structure analysis of the Fe-BTTA material was performed. The single-crystal structure of the nano-Fe-BTTA material was determined by single-crystal X-ray diffraction. Figure 2 As shown in (a), (b), and (c), this material crystallizes in the triclinic crystal system, space group P-1. The asymmetric unit of the crystal contains one iron ion and one completely deprotonated BTTA. 2- The ligand and one undeprotonated H₂BTTA ligand, the six-coordinated Fe ion, form an octahedral coordination configuration with two O atoms and four N atoms. These six atoms come from four BTTA ligands. 2- The ligand and two H2BTTA ligands have the molecular formula C 12H8N6O4. The three-dimensional framework structure of the nano-Fe-MOF material can be simplified to a 2,4,6-connected topology. The six-connected Fe single-metal nodes and the four-connected ligand BTTA... 2- The ligand H2BTTA, which is linked to the second ligand, forms a three-dimensional framework structure with irregular one-dimensional channels along the a and b directions. The global maximum cavity diameter is... The limiting diameter of the cavity is Accessible hole volume is
[0071] Meanwhile, the powder X-ray diffraction (PXRD) pattern of the nano-Fe-BTTA material matches well with the X-ray diffraction pattern fitted to the single-crystal structure, proving its high phase purity. To test the chemical stability of its crystalline structure, the nano-Fe-BTTA material was immersed in water, acetone, dichloromethane, and ethanol for three days each, then filtered, dried, and its PXRD was tested. Figure 4 As shown, the lack of significant change in the PXRD pattern after solvent treatment indicates that its crystal structure remains unchanged, demonstrating excellent chemical stability.
[0072] from Figure 3 It can be seen that using STB as an auxiliary agent yields the target product, while without STB, only the ligand peak is observed. This indicates that ligand insolubility leads to a low degree of reaction or even no reaction at all. The addition of STB improves this shortcoming. Figure 5 It can be seen that the product obtained by using STB is a uniform block with a small uniform nanoscale size, while the product obtained by not using STB has a disordered morphology.
[0073] Furthermore, the higher the charge density on the particle surface, the greater the Zeta potential, and the stronger the charge repulsion between particles, making it less likely for particles to aggregate. Figure 6 It can be seen that the sample without STB has a lower zeta potential, and therefore tends to aggregate, meaning the particle size should be larger. Combined with particle size distribution (DLS) data... Figure 7 As can be seen, the sample with added STB has a significantly smaller particle size, reaching a uniform nanoscale.
[0074] The following is a further investigation into the aqueous ultrasonic synthesis of nano-Fe-BTTA materials using iron salts, ligands, and the auxiliary agent STB, in order to determine the optimal method, as detailed below:
[0075] Example 2:
[0076] The difference between Example 2 and Example 1 is that the iron salt used is iron acetylacetonate, while the other conditions are the same.
[0077] Example 3:
[0078] The difference between Example 3 and Example 1 is that the iron salt used is ferric sulfate, while the other conditions are the same.
[0079] Example 4:
[0080] The difference between Example 4 and Example 1 is that the iron salt used is ferric nitrate, while the other conditions are the same.
[0081] Table 1 Effect of metal salt on yield
[0082] Metal salts Yield (%) Example 1 Ferric chloride 88 Example 2 Iron acetylacetonate 82 Example 3 Ferric sulfate 83 Example 4 Ferric nitrate 80
[0083] The purpose of setting up Examples 1 and Examples 2-4 was to explore the effect of iron salts on the reaction. The results are shown in Table 1. Different iron salts had little effect on the yield. After comprehensive comparison, ferric chloride was the preferred option.
[0084] Example 5:
[0085] The difference between Example 5 and Example 1 is that the molar ratio of iron salt to ligand is 1:0.2, while the other conditions are exactly the same.
[0086] Example 6:
[0087] The difference between Example 6 and Example 1 is that the molar ratio of iron salt to ligand is 1:1.5, while the other conditions are exactly the same.
[0088] Example 7:
[0089] The difference between Example 7 and Example 1 is that the molar ratio of iron salt to ligand is 1:2, while the other conditions are exactly the same.
[0090] Table 2 Effect of metal salt ligand molar ratio on yield
[0091] Metal salt ligand molar ratio Yield (%) Example 1 1:1 88 Example 5 5:1 44 Example 6 1:1.5 79 Example 7 1:2 55
[0092] The purpose of setting up Examples 1 and Examples 5-7 was to investigate the effect of the molar ratio of iron salt to ligand on the reaction. The results are shown in Table 2. Different molar ratios of iron salt to ligand have a significant impact on the yield. After comprehensive comparison, a ratio of 1:1 is preferred.
[0093] Example 8:
[0094] The difference between Example 8 and Example 1 is that the ultrasonic power is 200W, while the other conditions are exactly the same.
[0095] Example 9:
[0096] The difference between Example 9 and Example 1 is that the ultrasonic power is 400W, while the other conditions are exactly the same.
[0097] Example 10:
[0098] The difference between Example 10 and Example 1 is that the ultrasonic power is 700W, while the other conditions are exactly the same.
[0099] Example 11:
[0100] The difference between Example 11 and Example 1 is that the ultrasonic power is 800W, while the other conditions are exactly the same.
[0101] Table 3. Effect of ultrasonic power on yield
[0102] Ultrasonic power (W) Yield (%) Example 1 600 88 Example 8 200 59 Example 9 400 73 Example 10 700 86 Example 11 800 86
[0103] The purpose of setting up Examples 1 and Examples 8-11 was to investigate the effect of ultrasonic power on the reaction. The results are shown in Table 3. As the ultrasonic power increases, the product first increases and then decreases. Therefore, the preferred ultrasonic power is 600W.
[0104] Example 12:
[0105] The difference between Example 12 and Example 1 is that the reaction time is 30 minutes, while the other conditions are exactly the same.
[0106] Example 13:
[0107] The difference between Example 13 and Example 1 is that the reaction time is 60 minutes, while the other conditions are exactly the same.
[0108] Example 14:
[0109] The difference between Example 14 and Example 1 is that the reaction time is 90 minutes, while the other conditions are exactly the same.
[0110] Table 4 Effect of reaction time on yield
[0111] Reaction time (min) Yield (%) Example 1 5 88 Example 12 30 86 Example 13 60 84 Example 14 90 84
[0112] The purpose of setting up Examples 1 and Examples 12-14 was to investigate the effect of reaction time on the reaction. The results are shown in Table 4. As the synthesis time increases, the yield decreases slightly. Therefore, the preferred synthesis time is 5 min.
[0113] Example 15:
[0114] The difference between Example 15 and Example 1 is that the reaction system is scaled up by 10 times, while the other conditions are exactly the same.
[0115] Example 16:
[0116] The difference between Example 16 and Example 1 is that the reaction system is scaled up by 20 times, while the other conditions are exactly the same.
[0117] Example 17:
[0118] The difference between Example 17 and Example 1 is that the reaction system is scaled up by 100 times, while the other conditions are exactly the same.
[0119] Example 18:
[0120] The difference between Example 18 and Example 1 is that the reaction system is scaled up by 200 times, while the other conditions are exactly the same.
[0121] Table 5. Space-time yields obtained with different reaction solution volumes.
[0122]
[0123]
[0124] Examples 1 and 15-18 were set up to investigate the effect of different reaction solution volumes on the space-time yield of the product. The results are shown in Table 5. It can be seen that proportionally increasing the reaction solution volume can effectively improve the space-time yield; the space-time yield for a total reaction solution volume of 4L has been tested to be as high as 99.2 kg / (m³). 3 ·h).
[0125] The above are comparative examples and embodiments of the synthesis of nano-Fe-BTTA materials with and without the use of STB auxiliaries. The synthesis ideas and mechanisms are also applicable to the synthesis of other nano-MOF materials. The following comparative examples and embodiments will be used to verify its universality.
[0126] Comparative Example 19:
[0127] Nano-MOF materials are prepared without using STB.
[0128] 1. Weigh 0.5 mol ZrCl4 and 0.5 mol H2BDC (phthalic acid) into a 25 mL sieve-sealed reagent bottle, add 15 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 10 min, and the sonicator power is set to 600 W.
[0129] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid product is dried in an oven or freeze-dried to obtain the target product.
[0130] Example 19:
[0131] Using STB, nano-MOF materials were prepared.
[0132] 1. Weigh 0.5 mol ZrCl4 and 0.5 mol H2BDC into a 25 mL sieve-sealed reagent bottle, then weigh 0.5 mol STB into the sieve-sealed reagent bottle and add 15 mL of ultrapure water. Turn on the sonicator to synthesize the product. The reaction time is 10 min and the sonicator power is set to 600 W.
[0133] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0134] from Figure 8 It can be seen that the target product can be obtained by using STB as an auxiliary agent, while the crystallinity of the sample without STB is very poor, indicating that STB has a great promoting effect on the normal progress of the reaction; from Figure 9 It can be seen that the product obtained by using STB is a uniform block with a small, uniform nanoscale size, while the product obtained by not using STB has a disordered and uneven morphology.
[0135] Comparative Example 20:
[0136] Nano-MOF materials are prepared without using STB.
[0137] 1. Weigh 3 mol (NH4)2Ce(NO3)6 and 3 mol H2FA (fumaric acid) into a 25 mL thread-sealed reagent bottle, add 10 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 5 min, and the sonicator power is set to 400 W.
[0138] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0139] Example 20:
[0140] Using STB, nano-MOF materials were prepared.
[0141] 1. Weigh 3 mol of (NH4)2Ce(NO3)6 and 3 mol of H2FA into a 25 mL sieve-sealed reagent bottle. Then weigh 3 mol of STB and add it to the sieve-sealed reagent bottle along with 10 mL of ultrapure water. Turn on the sonicator to synthesize the mixture. The reaction time is 5 min and the sonicator power is set to 400 W.
[0142] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0143] from Figure 10It can be seen that using STB ligands yields the target product, while the sample without STB only shows ligand peaks, indicating that STB has a significant promoting effect on the normal progress of the reaction; from Figure 11 It can be seen that the product obtained by using STB is a uniform nano-sized block, while the product obtained without using STB has a disordered and uneven morphology.
[0144] Comparative Example 21:
[0145] Nano-MOF materials are prepared without using STB.
[0146] 1. Weigh 1 mol Mg(NO3)2 and 1 mol H2OBA (4,4'-dicarboxylic acid diphenyl ether) into a 25 mL sieve-sealed reagent bottle, add 20 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 20 min, and the sonicator power is set to 600 W.
[0147] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0148] Example 21:
[0149] Using STB, nano-MOF materials were prepared.
[0150] 1. Weigh 1 mol Mg(NO3)2 and 1 mol H2OBA into a 25 mL sieve-sealed reagent bottle. Then weigh 1 mol STB and add it to the sieve-sealed reagent bottle along with 20 mL of ultrapure water. Turn on the sonicator to synthesize the mixture. The reaction time is 20 min and the sonicator power is set to 600 W.
[0151] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0152] from Figure 12 It can be seen that the target product can be obtained by using STB ligand, while the sample without STB failed to form the target product and had extremely poor crystallinity; from Figure 13 It can be seen that the product obtained using STB is a uniform block with a small, uniform nanoscale size, while the product obtained without STB contains unreacted substances.
[0153] Comparative Example 22:
[0154] Nano-MOF materials are prepared without using STB.
[0155] 1. Weigh 4 mol Mg(NO3)2 and 1 mol H4GA (gallic acid) into a 25 mL sieve-sealed reagent bottle, add 20 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 5 min, and the sonicator power is set to 600 W.
[0156] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0157] Example 22:
[0158] Using STB, nano-MOF materials were prepared.
[0159] 1. Weigh 4 mol Mg(NO3)2 and 1 mol H4GA into a 25 mL sieve-sealed reagent bottle. Then weigh 1 mol STB and add it to the sieve-sealed reagent bottle along with 20 mL of ultrapure water. Turn on the sonicator to synthesize the mixture. The reaction time is 5 min and the sonicator power is set to 600 W.
[0160] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0161] from Figure 14 It can be seen that using STB as an auxiliary agent yields the target product, while without STB, only the ligand peak is observed. This indicates that ligand insolubility leads to a low degree of reaction or even no reaction at all. The addition of STB improves this shortcoming. Figure 15 It can be seen that the product obtained by using STB is a uniform block with a small, uniform nanoscale size, while the product obtained by not using STB has an inconsistent morphology and uneven size.
[0162] Comparative Example 23:
[0163] Nano-MOF materials are prepared without using STB.
[0164] 1. Weigh 1 mol Mg(NO3)2 and 1 mol DHBQ (2,5-dihydroxy-1,4-benzoquinone) into a 25 mL sieve-top reagent bottle, add 20 mL of ultrapure water, turn on the sonicator to synthesize, the reaction time is 5 min, and the sonicator power is set to 600 W.
[0165] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0166] Example 23:
[0167] Using STB, nano-MOF materials were prepared.
[0168] 1. Weigh 1 mol Mg(NO3)2 and 1 mol DHBQ into a 25 mL threaded reagent bottle. Then weigh 1 mol STB and add it to the beaker threaded reagent bottle, along with 20 mL of ultrapure water. Turn on the sonicator to synthesize the mixture. The reaction time is 5 min, and the sonicator power is set to 600 W.
[0169] 2. After the reaction is complete, the product is filtered or centrifuged, and the solid sample is dried in an oven or freeze-dried to obtain the target product.
[0170] from Figure 16 It can be seen that using STB as an auxiliary agent yields the target product, while without STB, only the ligand peak is observed, indicating that the insolubility of the ligand leads to a low degree of reaction or even no reaction occurring. Figure 17 It can be seen that the product obtained by using STB is a uniform block with a small, uniform nanoscale size, while the product obtained by not using STB has a disordered morphology and is relatively larger.
[0171] It is understood that the various method embodiments mentioned above in this disclosure can be combined with each other to form combined embodiments without violating the principle and logic. Due to space limitations, this disclosure will not elaborate further. The embodiments of this disclosure have been described above. The above description is exemplary and not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical applications, or technical improvements to the embodiments in the market, or to enable other those skilled in the art to understand the embodiments disclosed herein.
Claims
1. A nano-Fe-MOF material, characterized in that: The material is an aqueous ultrasonic reaction product of an iron salt, a 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid ligand, and a strongly basic organometallic compound, with the molecular formula C. 12 H8N6O4 crystallizes in the triclinic crystal system, space group P-1. The asymmetric unit of the crystal contains one iron ion and one completely deprotonated BTTA. 2- The ligand and an undeprotonated H2BTTA ligand, the six-coordinated Fe ion with two O atoms and four N atoms form an octahedral coordination configuration, the six-connected Fe single metal node and the four-connected BTTA ligand 2- The ligand H2BTTA, which is linked to the two, coordinates to form a three-dimensional framework structure with one-dimensional irregular channels.
2. The nano-Fe-MOF material according to claim 1, characterized in that: The iron salt is one of ferric chloride, ferric acetylacetone, ferric sulfate, and ferric nitrate; and / or, The strongly alkaline organometallic compound is sodium alkoxide or potassium alkoxide; and / or, The molar ratio of the iron salt to the ligand is 1:(0.2-2).
3. The nano-Fe-MOF material according to claim 2, characterized in that: The iron salt is ferric chloride; and / or, The sodium alkoxide is sodium tert-butoxide, sodium methoxide, or sodium ethoxide; and the potassium alkoxide is potassium tert-butoxide; and / or, The molar ratio of the iron salt to the ligand is 1:
1.
4. The nano-Fe-MOF material according to claim 3, characterized in that: The sodium alkoxide is sodium tert-butoxide; and / or, The ultrasonic power is 200-800W; and / or, The reaction time is 5-90 min.
5. The nano-Fe-MOF material according to claim 4, characterized in that: The ultrasonic power is 600W; and / or, The reaction time is 5 minutes.
6. A method for preparing nano-MOF materials, characterized in that, include: The reaction system consisting of a metal salt, ligand, sodium or potassium alkoxide auxiliaries, and water is carried out under ultrasonic conditions. The target product is obtained by drying the solid phase product in the reaction product.
7. The method for preparing nano-MOFs materials according to claim 6, characterized in that: The metal salt is one of cerium ammonium nitrate, zirconium chloride, and magnesium nitrate; and / or, The additive is STB.
8. The method for preparing nano-MOFs materials according to claim 6 or 7, characterized in that: The ligand is one of terephthalic acid, gallic acid, fumaric acid, 4,4'-dicarboxylic acid diphenyl ether, 2,5-bis(1,2,4-triazol-1-yl)terephthalic acid, and 2,5-dihydroxy-1,4-benzoquinone.
9. The method for preparing nano-MOFs materials according to claim 8, characterized in that: The molar ratio of the metal salt to the ligand is 1:(0.2-2).
10. The method for preparing nano-MOFs materials according to claim 9, characterized in that: The ultrasonic power is 200-800W; and / or, The reaction time is 5-90 min.